KEBERHASILAN UMAR IBN KHATHTHAB MEMAJUKAN PEMERINTAHAN ISLAM - Syamruddin Nasution (An-Nida', 2011)
Umar is known other than as a conqueror, he was also known as a builder of a formidable government administration. So it's not excessive when compared with the three al-Khilafat al-Rashidin before and after, the reign of Omar's most stable and good. He is renowned as a fair and wise leader, a simple life, He is also known to care for the little people and the poor and the welfare of their lives. In the reign of Umar had materialized the ideal Islamic government, the officials are not arbitrarily executions in the reign, the rich are not arbitrary in behaving, the poor are not persecuted in the life, they stand as upright, seated at a low.